2018
DOI: 10.1038/s41598-018-35556-4
|View full text |Cite
|
Sign up to set email alerts
|

Changes in retinal flow density measured by optical coherence tomography angiography in patients with carotid artery stenosis after carotid endarterectomy

Abstract: The aim of the study presented here was to evaluate retinal and optic nerve head (ONH) perfusion in patients with severe asymptomatic carotid artery stenosis (CAS) compared with healthy controls and to analyze the impact of carotid endarterectomy using optical coherence tomography angiography (OCT-A). 25 eyes of 25 patients with CAS (study group) and 25 eyes of 25 healthy controls (control group) were prospectively included in this study. OCT-A was performed using RTVue XR Avanti (Optovue, Inc, Fremont, Califo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
57
1
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(67 citation statements)
references
References 28 publications
6
57
1
3
Order By: Relevance
“…Assuming that retinal microvasculature changes in response to systemic microvascular function, increased retinal vessel density in both eyes may attribute to the longitudinal effect of medications. In consistent with our findings, a recent study using OCTA observed a reduced vessel density in patients with CAS when compared with healthy controls and the vessel density increased significantly after CEA in the ipsilateral and in the contralateral eye 22 .…”
Section: Discussionsupporting
confidence: 93%
“…Assuming that retinal microvasculature changes in response to systemic microvascular function, increased retinal vessel density in both eyes may attribute to the longitudinal effect of medications. In consistent with our findings, a recent study using OCTA observed a reduced vessel density in patients with CAS when compared with healthy controls and the vessel density increased significantly after CEA in the ipsilateral and in the contralateral eye 22 .…”
Section: Discussionsupporting
confidence: 93%
“…To the best of our knowledge, only one investigation has been conducted in order to assess OCTA changes in CAS patients ( Lahme et al, 2018 ). This study agreed in terms of including only asymptomatic patients, although their follow-up was limited just to 3–4 days after surgery, whereas our follow-up was longer ( Lahme et al, 2018 ). This previous investigation disclosed similar results regarding RPC blood flow impairment before surgery and its restoration after endarterectomy in the ipsilateral.…”
Section: Discussionmentioning
confidence: 99%
“…With the development of new technology in ophthalmology, many potential lesions can be detected before visible fundus diseases occur. Asymptomatic patients with carotid stenosis were found to have reduced retinal vascular density (Lahme et al 2018), thin retinal nerve fibre layers (Wang et al 2017a), and reduced and delayed electroretinographic responses (Kofoed et al 2013), suggesting that carotid stenosis affects the microstructure and function of the retina. However, whether carotid artery stenosis affects retinal oxygen metabolism remains unclear.…”
Section: Introductionmentioning
confidence: 99%